Analisis Perubahan Sifat Mekanik Al 6063 Setelah Dilakukan Heat Treatment Pada Temperatur Tetap Dengan Waktu Tahan Yang Bervariasi - Media Nofri (Bina Teknika, 2020)
Aluminium is a material commonly used in human activity. On operating condition, people expect that aluminium has mechanical properties such as hardness. The mechanical properties can be improved by doing some treatment processes, such as by heat treatment. Al alloys 6063 has a smaller strength than other alloys, but very lithe. Al alloys 6063 also has very good ability to forging, and can be strengthened by heat treatment after processing. AI alloys 6063 contains chemical compotition 98.7% Al, 0.530% Si and 0.532% Mg. AI alloys 6063 common used for frame construction, engine piston, cylinder head combustion engine, bicycle parts, etc, because alloys have excellent corrosion resistance properties than the other heated aluminium. In this research, Al 6063 will be heated on 530 ° C with variation holding time from 30 minutes to 60 minutes and then cooled by fresh air. Next, observing microstructure. Finally, from the research results found Al dendrite structure and spread particle of Si and the formation of particle enlargment. Heat treatment of Al 6063 doesn’t have big impact, heating process should be done with variation holding time over 60 minutes. Longer heating process will give higher hardness value or better.